Compaction parameters of reinforced clayey sand - Chegenizadeh, Amin; Nikraz, Hamid (Institute of Electrical and Electronics Engineers, Inc., 2011)
Composite soils have been widely used in civil engineering applications, especially in slopes, embankment dam and landfills. This paper aims to investigate effect of fiber inclusion on compaction characteristic of composite soil (i.e. sand composite). A series of laboratory tests carried out to evaluate fiber effect on optimum water content and maximum dry unit weight of composite soils. Sand was selected as soil part of the composite and plastic fiber was used as reinforcement. The fiber parameters differed from one test to another, as fiber length varied from 10 mm to 30mm and fiber content were selected as 1% and 3%. For each test, compaction curved derived and the results were compared. The results proved that inclusion of fiber affected compaction behavior of samples so that increasing in fiber content and length caused increasing in Optimum Moisture Content (OMC) and slightly decreased maximum dry unit weight.